Measuring program attainments (POs) of Bachelor of Chemical Engineering (Environment) using OBE – ANAS v14.0 tool / Mohaiyedin Idris ... [et al.] - Idris, Mohaiyedin; Zulhanip, Aida Zulia; Mokhtar, Nor Fadzilah; Wan Kamis, Wan Zuraida; Mohamad Nor, Norhusna (Universiti Teknologi MARA Cawangan Pulau Pinang, 2018)
Education system is recognised around the globe as an important element for a country’s development. Therefore, the prominence of education system around the world cannot be denied. In order to empower the education, the concept of Outcome Based Education (OBE) was first initiated by the academicians (who in particular?). Malaysia is also in line with other countries which pay close attention to the importance of OBE impact in the higher education institutions. The OBE implementation plays an important role in defining skills (psychomotor), knowledge (cognitive) and behavior (affective) for each graduate attributes. This paper is written to measure the program outcomes (POs) of Bachelor of Chemical Engineering (Enviroment) with honors (EH224) for its accreditation purpose. OBE concept system consists of significant aspects for measuring, monitoring and evaluating to determine whether or not the POs are attainable in producing the competencies of the selected graduates. The tool to fulfill the measuring POs is worked out by the Faculty of Electrical Engineering OBE committee members and known as OBE-ANAS system. A graphical user interface (GUI) is designed based on the Microsoft Visual C# programming language and Microsoft SQL Server 2012 (MSSQL 2012) is used as a database system. The tool is useful for measuring POs parameters such as POs average, POs density, individual POs and then, measuring the programme strength by implementing the measurement model which is the Degree of Programme Achievement (DPA).